2017
DOI: 10.1007/s10479-017-2497-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring productivity change accounting for adjustment costs: evidence from the food industry in the European Union

Abstract: This paper extends the measurement of dynamic productivity change over time to provide its full decomposition into economically meaningful components in the Data Envelopment Analysis framework. The dynamic approach accounts for dynamics of production decisions via adjustment costs and is visualized as a dynamic Luenberger productivity change indicator. The paper also estimates the dynamic productivity change and its components for a large dataset of European food companies from 2004 till 2012, grouped into Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The existence of a relationship between SCN and SCF by linking the use of technological advancements such as AI, emphasising Song et al (2019) concept on 'network brokerage' and Kapelko (2019) on ' competitive strategy for financing' with its implications for gaining access to financial resources, especially the generation of cash flow. This research approach supports the theory that a high innovative propensity leads to a chain of financing opportunities at the networks level on SCM, which in turn aggregate into the FDIs' persistent expansion.…”
Section: Food and Drink Supply Chain Meta-frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a relationship between SCN and SCF by linking the use of technological advancements such as AI, emphasising Song et al (2019) concept on 'network brokerage' and Kapelko (2019) on ' competitive strategy for financing' with its implications for gaining access to financial resources, especially the generation of cash flow. This research approach supports the theory that a high innovative propensity leads to a chain of financing opportunities at the networks level on SCM, which in turn aggregate into the FDIs' persistent expansion.…”
Section: Food and Drink Supply Chain Meta-frameworkmentioning
confidence: 99%
“…As customer demand continues to grow, FDIs need to find sustainable cash flows to meet demand. According to Kapelko (2019), post-recession supply chain finance is designed to support the supply chain by providing financial services at low-interest rates and with respect to cash flows and other financial activities. Dora et al (2019) argue that the principles of supply chain finance are a fundamental component of a sustainable food and drink supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Future research efforts could also be directed towards the extensions of latent class modeling into a three‐step approach in which the association between class membership and covariates is analyzed as a separate exercise to the estimation of latent classes (Vermunt, 2010). Furthermore, the analysis of dynamic productivity change over time (Kapelko, 2019; Oude Lansink et al, 2015) as a response variable in the latent class analysis could be an interesting line of future research. Within temporal analysis, further study could be directed towards the analysis of transitions of firms between classes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some articles have investigated the Spanish food manufacturing industry's dynamic productivity growth, including such contexts as the meat processing industry [25], meat processing and the oil and fat industries [26], and meat and dairy processing and the oil and fat industries [27]; all of this research shows that average productivity is not only very close to zero, but its components also have a negative technical change, a positive technical inefficiency change, and a positive scale inefficiency change [28]. Kapelko [28] analyzed the dynamic productivity growth of European food companies. He found that the overall trend of dynamic technical regress and positive dynamic technical inefficiency change across almost all regions and sectors.…”
Section: Literature Reviewmentioning
confidence: 99%